Avalanche current balancing using parallel connection of SiC-MOSFET/SiC-JFETs with cascode connection. (November 2021) - Sagara, Mitsuhiko; Wada, Keiji; Nishizawa, Shin-ichi; Saito, Wataru
Abstract: The realization of a DC breaker using semiconductors requires multiple power devices with low ON resistance to be connected in parallel. On the other hand, power devices that experience current interruption enter the avalanche mode to consume the energy stored in the parasitic inductance in the circuit wiring. In other words, a DC breaker requires the current balancing of multiple power devices connected in parallel during the avalanche mode. In this paper, a method to balance the current of power devices in avalanche mode is investigated. As a result, the use of SiC-JFET with cascode connections is found to be a suitable method by 400 V experimental system. Highlights: Semiconductor DC Breaker: A DC breaker consisting of a semiconductor device SiC-JFET:It is more reliable than MOSFETs for DC breaker applications. Parallel Connection: A large number of power devices can be connected in parallel to increase the current capacity. UIS Test: This test is applied to the evaluation of semiconductors as DC breakers.